Silahturahim dan disampaikannya Keutamaan Haji dan Umroh Terhadap Kekuatan Niat dan Kepahaman untuk Melaksanakannya Di Lingkungan IPB - Mardijja, Waladan; Hubeis, Musa; Indupurnahayu, Hj. (Jurnal Manajemen, 2016)
Results of the analysis showed friendship gives direct influence on the determination 0.02 and 0.042 against of understanding to implement them. That is friendship provide a less robust effect (not real) against the power of intention and does not provide significant effect (less powerful) against of understanding to implement them. The virtue of Hajj and Umrah directly affect the strength of the intention to implement 0.757 and 0,282 against of understanding to implement them. Determination impact directly against 0.604 of understanding to implement 60.4%, meaning that it conveys the virtue of Hajj provide a very strong influence on the strength of the intention to carry it out. The virtues of Hajj provide a strong enough influence on of understanding to implement them. Through the power of intention, friendship gives indirect influence on of understanding to implement it by 0.12, while it conveys the primacy of Hajj provide indirect influence on of understanding to implement at 0.4463.